Bioinsecticide Production from Cigarette Wastes - Badhane Gudeta; Solomon K; M. Venkata Ratnam (International Journal of Chemical Engineering)
Tobacco, one of the most significant nonfood crops, is critical to agriculture worldwide. The tobacco processing business creates a significant amount of hazardous tobacco waste containing nicotine, and only a tiny portion of it gets recycled. Nicotine, the primary component of tobacco products such as cigarettes, is an alkaloid and can be used as an insecticide. This research aims to extract nicotine from discarded cigarette butts and utilize it as an insecticide. Extraction, emulsification, and efficiency testing on cabbage aphids are all part of the procedure. The initial extraction tests used a solvent combination of ethanol and methanol in various ratios, with a 3 : 1 ratio yielding the best results. Temperature (30–60°C), extraction length (4–6 hrs), and sodium hydroxide concentration (1–3 M) are the independent variables studied for extraction parameters, and the optimal conditions are determined using Design-Expert, response surface approach central composite design (RSM-CCD). In addition, artificial neural network (ANN) studies with MATLAB were used to accurately forecast extraction yield. The extracted product was evaluated using a gas chromatography–mass spectrometry (GC-MS) and a UV/visible spectrophotometer. The ideal crude extract yield and nicotine content were 17.75 and 3.26%, respectively, at the optimal conditions of temperature 60°C, time 4 hrs, and NaOH concentration 2.83 M with desirability of 0.832. The nicotine extracted was emulsified by combining the crude extract with a combination of palm oil and surfactants. Density, viscosity, pH, flash point, and surface tension of the emulsified concentration were measured and reported as 1.01 ± 0.01 g/ml, 585.33 ± 2.52 mPa s, 9.37 ± 0.03, 87.96 C, and 34.10 mN/m, respectively. On the cabbage aphid, the emulsified concentrated extract performed best at a ratio of 1 : 100 (emulsified concentrated to solvent).